An Overview of the Mechanisms through Which Plants Regulate ROS Homeostasis under Cadmium Stress - Pan Luo; Jingjing Wu; Ting-Ting Li; Peihua Shi; Qi Ma; Dong-Wei Di (MDPI AG, 2024)
Cadmium (Cd2+) is a non-essential and highly toxic element to all organic life forms, including plants and humans. In response to Cd stress, plants have evolved multiple protective mechanisms, such as Cd2+ chelation, vesicle sequestration, the regulation of Cd2+ uptake, and enhanced antioxidant defenses. When Cd2+ accumulates in plants to a certain level, it triggers a burst of reactive oxygen species (ROS), leading to chlorosis, growth retardation, and potentially death. To counteract this, plants utilize a complex network of enzymatic and non-enzymatic antioxidant systems to manage ROS and protect cells from oxidative damage. This review systematically summarizes how various elements, including nitrogen, phosphorus, calcium, iron, and zinc, as well as phytohormones such as abscisic acid, auxin, brassinosteroids, and ethylene, and signaling molecules like nitric oxide, hydrogen peroxide, and hydrogen sulfide, regulate the antioxidant system under Cd stress. Furthermore, it explores the mechanisms by which exogenous regulators can enhance the antioxidant capacity and mitigate Cd toxicity.